Dual-polarization two-port fiber-optic gyroscope - Wang, Zinan (Springer, 2017)
This thesis demonstrates and investigates novel dual-polarization interferometric fiber-optic gyroscope (IFOG) configurations, which utilize optical compensation between two orthogonal polarizations to suppress errors caused by polarization nonreciprocity. Further, it provides a scheme for dual-polarization two-port IFOGs and details their unique benefits. Dual-polarization IFOGs break through the restriction of the "minimal scheme, " which conventional IFOGs are based on. These innovative new IFOGs have unique properties: They require no polarizer and have two ports available for signal detection. As such, they open new avenues for IFOGs to achieve lower costs and higher sensitivity.
"Doctoral thesis accepted by Peking University, China."
Keywords: Optical gyroscopes.; Optical fiber detectors.; elektronické knihy; electronic books